Molecular characterization of soybean cultivars by microsatellite markers with universal tail sequence Caracterização molecular de cultivares de soja por meio de marcadores microssatélites com sequência de cauda universal - Carlos Alexandre Gomes Ribeiro; Janaína Paula Marques Tanure; Talles Eduardo Ferreira Maciel; Everaldo Gonçalves de Barros (Pesquisa Agropecuária Brasileira, 2013)
The objective of this work was to standardize a semiautomated method for genotyping soybean, based on universal tail sequence primers (UTSP), and to compare it with the conventional genotyping method that uses electrophoresis in polyacrylamide gels. Thirty soybean cultivars were genotypically characterized by both methods, using 13 microsatellite loci. For the UTSP method, the number of alleles (NA) was 50 (2-7 per marker) and the polymorphic information content (PIC) ranged from 0.40 to 0.74. For the conventional method, the NA was 38 (2-5 per marker) and the PIC varied from 0.39 to 0.67. The genetic dissimilarity matrices obtained by the two methods were highly correlated with each other (0.8026), and the formed groups were coherent with the phenotypic data used for varietal registration. The 13 markers allowed the distinction of all analyzed cultivars. The low cost of the UTSP method, associated with its high accuracy, makes it ideal for the characterization of soybean cultivars and for the determination of genetic purity. O objetivo deste trabalho foi padronizar um método semi‑automatizado para genotipagem de soja, baseado na metodologia de iniciadores com sequências de cauda universal (PSCU), e compará‑lo ao método de genotipagem convencional de eletroforese em gel de poliacrilamida. Trinta cultivares de soja foram caracterizadas genotipicamente por ambos os métodos, com o uso de 13 locos microssatélites. Para o método PSCU, o número de alelos (NA) foi de 50 (2-7 por marcador) e o conteúdo de informação polimórfica (PIC) variou de 0,40 a 0,74. Para o método convencional, o NA foi de 38 (2-5 por marcador) e o PIC variou de 0,39 a 0,67. As matrizes de dissimilaridade genética obtidas pelos dois métodos apresentaram alta correlação entre si (0,8026), e os grupos formados foram coerentes com dados fenotípicos utilizados para o registro varietal. Os 13 marcadores permitiram a distinção de todas as cultivares analisadas. O baixo custo do método PSCU, associado a sua alta acurácia, torna‑o ideal para a caracterização de cultivares de soja e a determinação de pureza genética.